'Master of the Orchester with a Sallary': Handel at the Bank of England. Issue 1 (17th June 2020) - Harris, Ellen T
Abstract: The discovery of an account held by Handel at the Bank of England in 1721 offers new documentary information about his financial transactions and evidence for his residence before the move to Brook Street. Careful consideration of the circumstances surrounding this account leads to a reinterpretation of Handel's short-lived accounts with the Royal African Company in 1720 and sheds light on Handel's South Sea Annuities account (1723–32). An analysis of the South Sea Annuities account clarifies its origin and explains its pattern of credits and withdrawals, suggests the exact salary Handel received from the Royal Academy of Music as 'Master of the Orchester', and indicates that the financial arrangements for Handel's salary that had been in place from the inception of the Academy were continued at the beginning of the 'Second Academy'.